Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, Aset Pajak Tangguhan, Dan Komisaris Independen Terhadap Manajemen Laba - Ramadhina, Nurlaily; Tri Utami (LPPM POLITEKNIK LP3I BANDUNG, 2025)
The purpose of this research is to examine the impact of Tax Planning, Deferred Tax Expenses, Deferred Tax Assets, and Independent Commissioners on Profit Management in Energy Sector Companies listed on the Indonesia Stock Exchange (BEI) during the period from 2018 to 2023. This study utilizes secondary data, specifically the annual financial reports of the companies. It employs a quantitative research approach. The total population consists of 87 companies in the energy sector, with purposive sampling as the chosen method. The study uses a sample of 15 companies over a 6-year observation period, resulting in a total of 90 observation objects. The analysis technique applied in this research is panel data regression analysis, utilizing the common effect regression model. Data processing was carried out using Eviews version 13 and Microsoft Office Excel. The findings indicate that tax planning, deferred tax expenses, deferred tax assets, and independent commissioners have a simultaneous effect on earnings management. Specifically, tax planning does not influence earnings management, deferred tax expenses also do not impact earnings management, deferred tax assets do influence earnings management, and independent commissioners have no effect on earnings management.